2016
DOI: 10.1177/1948550616671997
|View full text |Cite
|
Sign up to set email alerts
|

Improving Girls’ Sense of Fit in Science

Abstract: A field experiment tested the effect of choosing a “favorite” role model on sense of fit in science among middle school girls. The girls participated in a 1-day science outreach event where they were exposed to multiple female role models. At the end of the event, participants were randomly assigned to choose and write about a favorite role model or to choose and write about their best friend. Girls in the role model choice condition experienced a significant increase in sense of fit in science, whereas girls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Role models can be inspirational and can reduce the selfstereotyping of stigmatized groups, and this may be the case for women in male-dominated STEM fields (Lockwood, 2006;Betz and Sekaquaptewa, 2012;O'Brien et al, 2017). Interventions based on role models revolve around enhancing a sense of belonging and identity in STEM fields, thereby fostering the personal connections of girls to the STEM community (Casad al., 2018;Van Camp et al, 2019).…”
Section: Role-model Influencementioning
confidence: 99%
“…Role models can be inspirational and can reduce the selfstereotyping of stigmatized groups, and this may be the case for women in male-dominated STEM fields (Lockwood, 2006;Betz and Sekaquaptewa, 2012;O'Brien et al, 2017). Interventions based on role models revolve around enhancing a sense of belonging and identity in STEM fields, thereby fostering the personal connections of girls to the STEM community (Casad al., 2018;Van Camp et al, 2019).…”
Section: Role-model Influencementioning
confidence: 99%
“…Very narrowly defined norms of success with steep "up-or-out" systems (such as in finance, consultancy, and academia) are very excluding and communicate that one should either adhere to a White heteronormative standard of success (which is likely to promote self-group distancing) or seek a career elsewhere. The presence of minority group role models in key positions in the organization can broaden the perspective on who fits these positions and improve performance, self-evaluations, and aspiration among low-status groups (Lockwood, 2006;O'Brien et al, 2016; for a review see Morgenroth, Ryan, & Peters, 2015 bias is so systematic that even minority members themselves justify their derogated position. These deeply rooted social biases should be tackled from the top down in formal governmental laws and regulations that ensure equal rights, but also from the bottom up, by changing the narrative in informal conversations at work, on the street, and at home, because daily conversations on the micro-level about what is considered "normal" can be a vehicle for social change on the macro-level (Koudenburg, Postmes, & Gordijn, 2017).…”
Section: Alternative S Tr Ateg Ie S and Interventi On Smentioning
confidence: 99%
“…Interventions that fail to facilitate identification with the role model may not result in a role model effect. Studies that have assessed interventions in which adolescent girls engaged in science tasks and interacted with female scientists revealed that girls did not immediately and spontaneously view the female scientists as potential role models (Buck et al, 2008; O’Brien et al, 2017). Specifically, girls only began to view the female scientists as role models after establishing personal connections with them (Buck et al, 2008).…”
Section: Effects Of Exposure To Role Models In Adolescence and Early mentioning
confidence: 99%